Bearing Capacity Of Partial Skirted Footing On Clay - Smadi, Bashar Mustafa, Anto Budi Listyawan, S.T., M.Sc (2017)
Bearing capacity is the most important factor in designing the foundation. It is necessary to find an effort to improve the bearing capacity. Skirts that are attached on the bellow of footing can be used as an alternative of it. They are used to improve the bearing capacity of shallow footing on soft clay soil. This study is performing nine laboratory experiments on steel circular footing with different diameters and different partially skirt length, on the soft clay soil by keeping the same formation of water content and compaction method. From the accomplished laboratory tests, it was found that partial skirts are very effective to improve the ultimate bearing capacity, as they increase the length, Skirts also reduce the settlement. The settlement generally decreases, when it is observed on the same value of load, 1 kN. Skirted circular footing with the longest skirt has the best condition of settlement.